Facebook - a platform for social connection - Johnson, Trevor (Henry Stewart Talks, 2009)
Online landscape, Facebook is about engagement and connections, The Facebook platform, The social graph, From advertising to marketing, Reach exactly who you want: mass or niche, Three levels of engagement on Facebook, Facebook platform tools, The future
Archived at 2022/04/11